Bagworm Cases as Pseudogastropods - Raymond W. Neck (Hello World!, 1975)
Recently, La Rocque (1973) reviewed several cases of pseudogastropods, animals originally believed to be gastropods due to gross external morphology. Additional examples were given by Corgan (1974).